Role of cell cycle perturbations in the combination therapy of chemotherapeutic agents and radiation. (September 2010) - Pauwels, Bea; Wouters, An; Peeters, Marc; Vermorken, Jan B; Lardon, Filip
The combination of radiotherapy with chemotherapeutic agents that sensitize tumor cells to ionizing radiation has long been regarded as a promising strategy to enhance cancer therapy. Many chemotherapeutic agents interact with radiation and enhance the cytotoxic or anti-tumor effect of radiation through a number of mechanisms. These include an increase in initial radiation damage, inhibition of cellular repair, cell cycle redistribution, enhancement of apoptosis, counteracting hypoxia and overcoming accelerated repopulation. This article focuses on the role of cell cycle perturbations in the radiosensitivity of cancer cells.